PSYCHOLOGICAL FEATURES OF STUDENTS’ PROTECTION AGAINST CYBERATTACKS (International journal of artificial intelligence, 2025)
The findings reveal a significant gap between students’ theoretical awareness of cyber threats and their actual protective behaviors. Higher levels of impulsivity were negatively correlated with safe cyber practices, while cognitive control and digital awareness positively predicted cyber resilience. Gender, academic discipline, and psychological coping strategies also emerged as influential factors. The study concludes that psychological preparedness, alongside technical education, plays a vital role in students' cybersecurity. It recommends the integration of cyberpsychological training, behavioral simulations, and personalized interventions into higher education systems to develop holistic cyber defense capabilities among students.